Transformation of Beauveria bassiana Bb9205 with pr1A, pr1J, and ste1 genes of Metarhizium anisopliae and evaluation of the pathogenicity on the coffee berry borer - RODRÍGUEZ-C., MARTHA LILIANA; GÓNGORA-B., CARMENZA E. (Revista Colombiana de Entomología, 2005)
Beauveria bassiana strain 9205 (Bb9205) was transformed with protease genes (pr1A and pr1J ) and one sterase gene (ste1) isolated from Metarhizium anisopliae that are involved in insect pathogenicity. The goal of this research was to increase the pathogenicity of the strain against the coffee berry borer, Hypothenemus hampei. To do this, genes were cloned into the plasmid pBarGPE1 that confers resistance to the herbicide ammonium-gluphosinate. A monosporic line of strain Bb9205 was obtained with pathogenicity of 78% mortality against H. hampei, using 1 x 106 spore/ml. Protoplasts were produced from this monosporic line. The methodology for the protoplast production was optimized obtaining 3 x 107 protoplasts/ml after enzymatic pretreatment for 4 hours under slow agitation at 37ºC. Transformation was carried out with the plasmids pBarGPE1pr1A, pBarGPE1-pr1J and pBarGPE1-ste1 by PEG and electroporation. Two strains transformed with the pr1A gene and one strain transformed with the ste1 gen were obtained, that showed resistance to 25 µg/ml of ammonium glufosinate. These strains showed increased proteolytic and sterolytic activity, respectively. Under laboratory conditions, pathogenicity tests of B. bassiana transformants was compared to untransformed monosporic Bb9205. Constitutive over-expression of protease in the transgenic strain Bb9205-pr1A improved its insecticidal activity. The transformed strain showed a 21,7% increase in the insect mortality rate with 14,3% reduction in the time of mortality. The Bb9205-ste1 transformant strain showed a 9,5% reduction of the time of mortality compared with the untransformed strain. The results indicate that breeding of Beauveria strains by genetic transformation can be achieved for purposes of better biological control.